OPTIMIZED PAPER NIR AND DIGITALIZATION TO ACHIEVE INDONESIA GOLD 2045 - Annisa Anita Dewi; Dani Muldiana (Jurnal PPI Dunia, 2018)
A technology-based mindset and pattern of work must be optimized to realize digitalization as a form of paperless optimization. At the current ASEAN level Indonesia is the first rank of paper exporters, ranking third in Asia after China and Japan while in the world of Indonesia is ranked sixth and aspires to be the second exporter of paper in the world. Behind it all is very important that the fact Indonesia is deforested from Kompas.com from 2010-2015 the width 684,000 he KTAR natural forest each yearand the extinction of various species most in Indonesia. This study focused on paper saving, optimization of digitalization with clear roadmap, as an effort to save the environment and go green . The research method used is case study with qualitative research design, using interview technique, observation, and documentation. From this research, it is found that paper optimization is strongly supported by various circles, optimization of digitalization is an increasingly sprightly effort to technology literacy, becoming a developed society, and protecting the environment from the consequences caused by deforestation such as species extinction, greenhouse effect, and natural disasters . However, the paper still needs to be used and should be used more effectively without neglecting the preservation of nature to achieve Indonesia Gold 2045.